Halal Beauty in the Digital Era: Influencer Promotion and Consumer Behavioral Responses - Novelika, Lutfiyah Rahma; Arristin , Arrinda Zahwa Nur Fauziah (Journal of social Philantrophy and Halal Research, 2025)
This qualitative study explores how influencer promotion strategies shape consumer responses in the halal cosmetics category among Indonesian Gen Z. Data were collected through netnography on Instagram and TikTok and through in depth interviews with consumers marketers and influencers. Using thematic analysis the study identifies three mechanisms that consistently appear in effective campaigns namely credible source signals communicative halal proof and community based narratives. These mechanisms operate through a trust pathway that links exposure to intention and action. The study contributes a practice oriented framework for halal beauty marketing and offers concrete guidance for evidence presentation creator selection and community engagement.